Tungsten Carbide and CNT–Graphene‐Supported Pd Electrocatalyst toward Electrooxidation of Hydrogen. Issue 9 (15th April 2015) - Han, Suenghoon; Youn, Duck Hyun; Lee, Min Hee; Lee, Jae Sung
Abstract Development of platinum‐free catalysts is urgently needed to make fuel cells a competitive technology for power generation in various fields. Here we report that combination of palladium and tungsten carbides supported on carbon nanotubes (CNT) graphene (GR) composite exhibits high activity for electrochemical hydrogen oxidation reaction. In the cyclic voltammetry, the electrochemical active surface area of Pd/WC/CNT–GR is much larger than that of other synthesized catalysts and even commercial Pt/C catalyst. In single cell operation, Pd/WC/CNT–GR shows 65 % of the maximum power density of the state‐of‐the‐art Pt/C catalyst and loses only 5 % of maximum power density after 50 h. Beneficial roles of WC and CNT–GR are discussed for the improved performance of palladium catalysts.